Diagnosis of personality disorders in adolescents: a study among psychologists - Laurenssen Elisabeth Martina Petronella; Hutsebaut Joost; Feenstra Dine Jerta; Van Busschbach Jan Jurgen; Luyten Patrick (BMC, 2013)
Abstract Background Recent guidelines concerning the treatment of personality disorders (PDs) recommend diagnosing PDs in adolescents. However, it remains unclear whether these guidelines influence the current opinions and practices of mental health care professionals. Methods Five hundred sixty-six psychologists completed an online survey concerning PDs in adolescents, of whom 367 professionals reported working with adolescents. The survey contained demographical questions (age, gender, profession, work setting) and specific questions related to PD in adolescence. Results Although a majority of psychologists working with adolescents acknowledged the existence of PDs in adolescents (57.8%), only a small minority diagnoses PDs in adolescence (8.7%) and offers a treatment specifically aimed at targeting PD pathology (6.5%). Reasons for not diagnosing PDs in adolescence mainly concerned the belief that adolescent personality problems are transient (41.2%) and that the DSM-IV-TR does not allow diagnosing PDs in adolescence (25.9%). Conclusions Although practice guidelines might have influenced clinicians' opinions about PDs in adolescence, they have had little impact so far on routine clinical practice.